Transformasi Digital pada Usaha Kecil: Studi Literatur dan Kasus RM Tapin Rasa dalam Meningkatkan Daya Tarik Pelanggan Melalui TikTok - Aditiya Kusuma,; Hastin Umi Anisah,; Mahdi Hidayatullah, (Jurnal Publikasi Ilmu Manajemen, 2024)
This study examines the implementation of digital transformation in small businesses through a case study of RM Tapin Rasa, a traditional restaurant leveraging TikTok as a marketing platform to enhance customer appeal. In the digital era, social media platforms like TikTok play a crucial role in consumer-oriented marketing strategies. With a "pull" approach, RM Tapin Rasa uses engaging content to foster close interactions with customers and strengthen brand awareness. Through this strategy, traditional businesses can maintain their local and unique aspects while using technology to reach a broader audience. Promotions on TikTok by @rm_tapin_rasa demonstrate that digital transformation need not sacrifice traditional values; rather, it can integrate them to bolster competitive advantage. This study also applies SWOT analysis to evaluate the strengths, weaknesses, opportunities, and challenges RM Tapin Rasa faces in using TikTok as a marketing tool. Findings reveal the importance of consumer-focused innovation for small businesses to remain relevant amidst rapid digital shifts, providing a model for effective technology adoption for other SMEs.